O028 Combination Pharmacological Therapy Targeting Multiple Mechanisms of Sleep Apnea. (9th November 2022) - Sands, S; Hess, L; Bertisch, S; Collet, J; Gell, L; Calianese, N; Vena, D; Azarbarzin, A; Taranto-Montemurro, L; Wellman, A; Landry, S; Thomson, L; et al.
Abstract: Introduction: Currently two leading experimental pharmacological interventions are under investigation for obstructive sleep apnea (OSA). Acetazolamide, which acts to stabilise ventilatory control, lowers the apnea-hypopnea index (AHI) by ∼38%. More recently, atomoxetine-plus-oxybutynin ("AtoOxy"), acting via improvements to dilator muscle responsiveness and baseline tone, was found to lower AHI by >50%. Given that each potential therapy targets a different pathophysiology, we tested whether combined AtoOxy-plus-acetazolamide would be more efficacious than AtoOxy alone. Methods: In a multicenter randomised crossover trial, 19 patients with moderate-to-severe OSA received AtoOxy (80/5mg respectively), acetazolamide (500mg), AtoOxy-plus-acetazolamide, or placebo at bedtime for 3 nights (half-dose on first night); outcomes were assessed at baseline and night 3 of each treatment period. Primary outcome: mixed model analysis compared the reduction in AHI(3% desaturation or arousal criterion) from baseline between AtoOxy-plus-acetazolamide and AtoOxy. Secondary outcomes included hypoxic burden, arousal index, and visual analog scale for sleep quality. Results: Compared with placebo, AHI was lowered with AtoOxy by +49 [33, 62] %baseline (estimate [95%CI]), AtoOxy-plus-acetazolamide by +47 [31, 61]%baseline, and acetazolamide by +34 [14, 50]%baseline. However, there was no effect of AtoOxy-plus-acetazolamide vs. AtoOxy alone (−3 [−33, 20]%baseline, P=0.8). Secondary outcomes: AtoOxy, acetazolamide and combined AtoOxy-plus-acetazolamide each lowered hypoxic burden and arousal index, but no differential effect of combination therapy was observed. There was no impact on the visual analog scale for sleep quality. Conclusions: While AtoOxy halved AHI, and acetazolamide lowered AHI by a third, the combination of these leading experimental interventions provided no greater efficacy than AtoOxy alone.